Using Functional Near-Infrared Spectroscopy to Study the Effect of Repetitive Transcranial Magnetic Stimulation in Concussion: A Two-Patient Case Study - Stilling, Joan M.; Duszynski, Chris C.; Oni, Ibukunoluwa; Paxman, Eric; Dunn, Jeff F.; Debert, Chantel T. (Frontiers in Neurology, 2019)
Background: Approximately 25% of concussion patients experience persistent post-concussion symptoms (PPCS). Repetitive transcranial magnetic stimulation (rTMS) has been explored as a treatment, and functional near-infrared spectroscopy (fNIRS) may be a cost-effective method for assessing response. Objectives: Evaluate rTMS for the treatment of PPCS and introduce fNIRS as a method of assessing treatment response. Methods: Design: Two-patient case study. Setting: Calgary Brain Injury Program. Participants: 47 and 49 yrs. male, with PPCS for 1-2 years (headache, cognitive difficulties, nausea, visual difficulties, irritability, anxiety, poor mood, sleep, and fatigue). Intervention: Ten sessions of rTMS therapy to the left dorsolateral prefrontal cortex (DLPFC), at 10Hz (600 pulses) and 70% of resting motor threshold amplitude. Participants completed an eight-week headache diary and a battery of clinical questionnaires prior to each fNIRS session. fNIRS: Hemodynamic changes were recorded over the frontoparietal cortex during rest, finger tapping, and a graded working memory test. fNIRS was completed pre-rTMS, following rTMS (day 14), and at 1-month post-rTMS (day 45). For comparison, two healthy, sex-matched controls were scanned with fNIRS once daily for five consecutive days. Results: Clinical scores improved (headache severity, MoCA, HIT-6, PHQ-9, GAD-7, QOLIBRI, RPSQ, BCPSI) or remained stable (PCL-5, headache frequency) post-rTMS, for both participants. Participant 1 reported moderate symptom burden, and a fNIRS task-evoked hemodynamic response showing increased oxyhemoglobin was observed following a working memory task, as expected. Participant 2 exhibited a high symptom burden pre-treatment, with abnormal fNIRS hemodynamic response where oxyhemoglobin declined, in response to task. One month following rTMS treatment, participant 2 had a normal fNIRS hemodynamic response to task, corresponding to significant improvements in clinical outcomes. Conclusion: This case study suggests fNIRS may be sensitive to physiological changes that accompany rTMS treatment. Further studies exploring fNIRS as a cost-effective technology for monitoring rTMS response in patients with PPCS are suggested.